Characterization of urban and rural organic particulate in the lower Fraser valley using two aerodyne aerosol mass spectrometers - Alfarra, M. R.; Coe, H.; Allan, J. D.; Bower, KN; Boudries, H; Canagaratna, M. R.; Jimenez, J. L.; Jayne, J. T.; Garforth, AA; Li, S. M.; Worsnop, D. R. (ATMOSPHERIC ENVIRONMENT, 2004)
Two Aerodyne Aerosol Mass Spectrometers (AMS) were deployed at three sites representing urban, semi-rural and rural areas during the Pacific 2001 experiment in the Lower Fraser Valley (LFV), British Columbia, Canada in August 2001. The AMS provides on-line quantitative measurements of the size and chemical composition of the non-refractory fraction of submicron aerosol particles. A significant accumulation mode with a peak around 400-500 nm was observed at all sites that was principally composed of sulphate, organics, ammonium and some nitrate. Another significant mode with a peak below 200 nm was also observed at the urban site and when urban plumes affected the other sites. This paper focuses on the variability of the organic particulate composition and size distribution as a function of location and photochemical activity with a particular emphasis on the urban and rural areas. The small organic mode at the urban site was well correlated with gas phase CO, 1,3-butadiene, benzene and toluene with Pearson's r values of 0.76, 0.71, 0.79 and 0.69, respectively, suggesting that combustion-related emissions are likely to be the main source of the small organic mode at this site. The mass spectra of the urban organic particulate are similar to those of internal combustion engine lubricating oil, and of diesel exhaust aerosol particles, implying that they were composed of a mixture of n-alkanes, branched alkanes, cycloalkanes, and aromatics. In contrast, organic particulate at the rural site was dominated by shorter chain oxidized organic compounds. Correlations between the two organic modes and gas phase compounds at the rural site indicated that a significant part of the small mode originated from combustion sources, while the large accumulation organic mode appeared to be the result of photochemical processing. Processing of organic particulate during a relatively high O-3 episode at the rural site appeared to increase the modal diameter of the accumulation mode from about 400 to 600 nm and almost doubled its mass loading. (C) 2004 Elsevier Ltd. All rights reserved.